MAKNA DAN NILAI PEDAGOGIS-TEOLOGIS DARI LAGU “DOA AKHIR TAHUN” KARYA DAUD SALEH LUJI - Daud Saleh Luji (Tambur : Journal of Music Creation, Study and Performance, 2022)
The purpose of this research is to find out the pedagogical-theological value of the song "End of Year Prayer" by Daud Saleh Luji which was composed and published in 2005. The research method used in this research is to use an analytical technique that is descriptive qualitative with a literature review approach. namely searching, analyzing, describing the pedagogical-theological value of the song and discussing it with a number of references. The results of the study show that the song "End of year prayer" has the following pedagogical-theological values ??1) Recognizing God as the possessor of power, 2) Always admit mistakes and apologize, 3) Ask God for forgiveness, 4) Entering the new year with new life , 5) Always believe that God is able to take care of every season of life